Internationalization of German Higher Education. - Hieber, Sabine (2011)
Among the over 1.8 million students enrolled at the 335 German institutions of higher education there is also a large number of foreign students. In the winter semester 1995/96, the number of foreign students was about 150,000; however, approximately 40% of them lived in Germany before embarking on academic studies and acquired their higher education entrance qualification in Germany. Foreign students account for a share of 8.2% of the total number of students in Germanyi). At the same time 42,600 German students were enrolled at higher education institutions abroadii). For Portugal this means: in 1995, 1,204 Portuguese students studied at German higher education institutionsiii) while 55 Germans studied in Portugal.iv)